2022
DOI: 10.1080/0267257x.2022.2046626
|View full text |Cite
|
Sign up to set email alerts
|

Children’s engagement with environmental issues

Abstract: This research offers insights into children's engagement with the environment by exploring whether and how children demonstrate individual and collective engagement with environmental issues. Using a child-centred methodological approach based on individual interviews and drawings, this research shows that children express different levels of engagement with environmental issues, such that they demonstrate varying levels of cognitive, emotional, and behavioural engagement. Our findings show evidence that indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…The systematic search identified studies reporting on approaches to engage young children with climate change. Upon screening the full texts, four peer-reviewed journal articles [26,[41][42][43] and one conference paper [44] met the inclusion criteria and were included in the narrative synthesis below. A backward selection found one book chapter [45], a report [46] and a book [47] that met the inclusion criteria (see Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The systematic search identified studies reporting on approaches to engage young children with climate change. Upon screening the full texts, four peer-reviewed journal articles [26,[41][42][43] and one conference paper [44] met the inclusion criteria and were included in the narrative synthesis below. A backward selection found one book chapter [45], a report [46] and a book [47] that met the inclusion criteria (see Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Children's sense of agency and their socialisation processes towards the environment within the family context were also important in sustaining their engagement with environmental issues. Schill, Muratore, and Hogg [42] explored whether and how French children engaged with environmental issues from a child-centred perspective, suggesting the importance of supporting and encouraging children's engagement in environmental issues at the individual and collective levels. Schill et al [42] reported that children's engagement with environmental issues was influenced by individual factors, such as knowledge, interest, perceived responsibility and behavioural control, as well as socio-contextual factors, such as communication within the family and socialisation processes.…”
Section: Summary Of Empirical Findingsmentioning
confidence: 99%
See 1 more Smart Citation